Parallel Patterns for Agent-based Evolutionary Computing - Stypka, Jan; Anielski, Piotr; Mentel, Szymon; Krzywicki, Daniel; Turek, Wojciech; Byrski, Aleksander; Kisiel-Dorohinicki, Marek (Computer Science, 2016)
Computing applications such as metaheuristics-based optimization can greatly benefit from multi-core architectures available on modern supercomputers. In this paper, we describe an easy and efficient way to implement certain population-based algorithms (in the discussed case, multi-agent computing system) on such runtime environments. Our solution is based on an Erlang software library which implements dedicated parallel patterns. We provide technological details on our approach and discuss experimental results.